Dietary Patterns, Adherence to the Food-Based Dietary Guidelines, and Ultra-Processed Consumption During the COVID-19 Lockdown in a Sample of Spanish Young Population - López-Gil, José Francisco; García-Hermoso, Antonio; Tárraga-López, Pedro Juan; Brazo-Sayavera, Javier (Frontiers in Pediatrics, 2021)
Purpose: The aim of this study was to explore the dietary patterns, adherence to Food-Based Dietary Guidelines, and the ultra-processed consumption during the COVID-19 lockdown among a Spanish young population aged 3–17 years. Methods: Parents/legal guardians of preschoolers, children, and adolescents aged 3–17 years were enrolled through social networks. The eating habits were assessed by a Food Propensity Questionnaire applied in the ENALIA (Encuesta Nacional de Alimentación en la población Infantil y Adolescente) Spanish survey, which aims to collect food intake information and other data about eating habits on children and adolescents (0–18 years old). Participants were dichotomized following the Food-Based Dietary Guidelines for the Spanish young population offered by the Spanish Society of Community Nutrition. The ultra-processed food score was determined following the principles established in the NOVA classification. Results: Data from 604 children and adolescents were included. An association between age group and the recommendations of snacks (p = 0.002), fruits (p = 0.010), and diaries (p < 0.001) was found. Adolescents showed a lower mean compliance with these guidelines than children (p = 0.004) and preschoolers (p < 0.001). Similarly, children reported lower Food-Based Dietary Guidelines than preschoolers (p = 0.015). Regarding ultra-processed consumption, it was also observed a higher intake in adolescents than in children (p = 0.037), as well as in preschoolers (p < 0.001). Conclusions: The associations that were found highlight the low proportion of the young population (especially adolescents) meeting the Food-Based Dietary Guidelines and the high consumption of ultra-processed foods during COVID-19 lockdown.